Mortality in Yusho patients exposed to polychlorinated biphenyls and polychlorinated dibenzofurans: a 50-year retrospective cohort study - Onozuka, Daisuke; Nakamura, Yuko; Tsuji, Gaku; Furue, Masutaka (Environmental health, 2020)
Background In 1968, the Yusho incident resulted in accidental exposure to polychlorinated biphenyls (PCBs), polychlorinated dibenzofurans (PCDFs), and related compounds in Japan. This study updated the risk of mortality in Yusho patients. Methods We obtained updated cohort data for all Yusho patients for the period 1968–2017. We calculated standardized mortality ratios (SMRs) for all-cause and cause-specific mortality over a 50-year follow-up period compared with the general population in Japan. Results A total of 1664 Yusho patients with 63,566 person-years of follow up were included in the analysis. Among males, excess mortality was observed for all cancers (SMR: 1.22, 95% confidence interval [CI]: 1.02 to 1.45) and lung cancer (SMR: 1.59, 95% CI: 1.12 to 2.19). Among females, increased mortality was observed for liver cancer (SMR: 2.05, 95% CI: 1.02 to 3.67). No significant increase was seen in non-cancer-related mortality compared with the general population. Conclusions Carcinogenic risk in humans after exposure to PCBs and PCDFs remains higher among Yusho patients. Our findings suggest the importance of care engagement and optimum management to deal with the burden of Yusho disease.